The place of memory in John Burnside’s the locust room - Aldhafeeri, Hilalah; Termizi, Arbaayah Ali (Universiti Putra Malaysia Press, 2016)
This article explores the interdisciplinary ecocriticism in John Burnside’s novel The Locust Room (2001). The article’s main focus will be on ecocriticism and psychoanalysis as a conceptual framework. Using ecocriticism, the concepts of dwelling and ecoconsciousness will be applied as ecocritical concepts to analyse the environmental nature depicted in the novel. On the other hand, the concept of anxiety will be utilized to explore the psychological anxious feelings of the novel’s protagonist, Paul. The protagonist’s psychological anxiety develops throughout the plot. The cause of his anxious sufferings is the male-rape phenomenon which is common at his university campus. To get rid of his anxiety, the protagonist tends to live in alienation to escape rape, and he decides to live in natural settings alone with animals and insects. Accordingly, the study follows a textual analysis of the environmental settings to argue nature as an exit for the protagonist’s anxiety. The interdisciplinary interconnection between ecocriticism and psychoanalysis will be elaborated by citing Cheryll Glotfelty’s concept of ecoconsciousness, Greg Garrard’s concept of dwelling, and Sigmund Freud’s concept of anxiety.